Akuntansi Dialogis dalam Pengelolaan Sumber Daya Kelautan untuk Ekonomi Biru Berkelanjutan - Fety Widianti Aptasari (SUBSTANSI, 2025)
Research objective: This study aims to explore dialogic accounting as a solution to enhance transparency, accountability, and sustainability in the management of coastal resources in Indonesia. Method: Data were collected through a literature review of journals, reports, and policies related to fisheries management and sustainability accounting. Data analysis was conducted using a qualitative approach based on thematic synthesis of the challenges and opportunities in implementing dialogic accounting. Research findings: The study found that information access inequality, top-down policy dominance, and resistance to change are major barriers to the implementation of dialogic accounting; however, information technology opens opportunities for transparency and stakeholder participation. Practical implication: The findings encourage the integration of dialogic accounting to achieve fairer, more participatory, and sustainable coastal resource governance.